2021
DOI: 10.1016/j.jcrimjus.2020.101756
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on European police officers: Stress, demands, and coping resources

Abstract: Purpose Facing the COVID-19 pandemic, police officers are confronted with various novel challenges, which might place additional strain on officers. This mixed-method study investigated officers' strain over three months after the lockdown. Methods In an online survey, 2567 police officers (77% male) from Austria, Germany, Switzerland, the Netherlands, and Spain participated at three measurement points per country in spring, 2020. Three-level growth curve models assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
135
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(152 citation statements)
references
References 40 publications
8
135
1
8
Order By: Relevance
“…Our study showed that 87.2% of the participants reported their level of stress and/or anxiety increased in their work because of not having the basic supplies for their personal protection. This is one of the reasons why the levels of death anxiety and burnout were elevated, as also reported in previous studies [5,21].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study showed that 87.2% of the participants reported their level of stress and/or anxiety increased in their work because of not having the basic supplies for their personal protection. This is one of the reasons why the levels of death anxiety and burnout were elevated, as also reported in previous studies [5,21].…”
Section: Discussionsupporting
confidence: 82%
“…These professions, considered essential, have not been exempt from the stress caused by COVID-19 in society; they have had to perform their work anomalously due to the pandemic, experiencing alterations in their usual tasks. In these circumstances, the Armed Forces, the FFCCSE, and the FFCCS have had to work, facing a situation that could affect their mental health and they have been at greater risk of stress because of the long exposure to the virus [19][20][21] and the new policies adopted to improve coexistence and protection of citizens when they needed them most. In this situation, there are two vital aspects to consider: if, in this pandemic context, the stress factors related to work changed, and if the level of stress of the security forces has increased [19].Under these circumstances, while the population was kept in confinement after the declaration of a state of alarm by the Spanish government, these workers had to continue working, while new stressors emerged: new protocols of action, changes in shifts, lack of personal protective equipment (PPE, including lack of hydroalcoholic gels and gloves), infected colleagues, lack of PCR (polymerase chain reaction) tests, and an increasing number of deaths every day.…”
Section: Introductionmentioning
confidence: 99%
“…Although we now know more about the public's experiences of the pandemic (see e.g. Seale et al 2020), the perspective of police officers in the UK has not yet been considered in any detail (see Frenkel et al 2020 for police officer experiences outside of the UK context). We examine whether the organisational climate police officers were operating in, and the government's response to COVID-19, had an impact on police officer health and well-being and their commitment to democratic modes of policing when faced with policing a pandemic.…”
Section: The Present Studymentioning
confidence: 99%
“…It seems inevitable that a global crisis like the COVID-19 pandemic will have affected police practices and the mental health of officers: among the many stressful experiences police are exposed to in their line of work, COVID-19 was unprecedented in terms of its scale and complexity, presenting simultaneous 'job content' and 'job context' stressors (Frenkel et al 2020). Compounding normal risk factors, police had to work and respond to calls for service under the threat of virus exposure.…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, executing COVID-19 related health regulations as early as possible maximizes its effectiveness ( Duy et al, 2015 ). However, the effectiveness of the regulation cannot be guaranteed without the support from Police & Military ( Frenkel et al, 2020 ). From this example, we identified possible loss scenarios for the inadequate cooperation between ‘Government’ and ‘Police & Military’.…”
Section: Discussionmentioning
confidence: 99%